2001
DOI: 10.1074/jbc.m104061200
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-like Activity of Tubulin

Abstract: The eukaryotic cytoskeletal protein tubulin is a heterodimer of two subunits, ␣ and ␤, and is a building block unit of microtubules. In a previous communication we demonstrated that tubulin possesses chaperonelike activities by preventing the stress-induced aggregation of various proteins (Guha, S., Manna, T. K., Das, K. P., and Bhattacharyya, B. (1998) J. Biol. Chem. 273, 30077-30080). As an extension of this observation, we explored whether tubulin, like other known chaperones, also protected biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Perhaps the folding of bound substrates take place within the ␣-crystallinsubstrate complex without dissociation. This model is consistent with the "marsupium" (kangaroo's bag) model (51) found to be valid for enzyme reactivation by other chaperones such as tubulin (52) and nucleolar protein B23 (53).…”
Section: Discussionsupporting
confidence: 85%
“…Perhaps the folding of bound substrates take place within the ␣-crystallinsubstrate complex without dissociation. This model is consistent with the "marsupium" (kangaroo's bag) model (51) found to be valid for enzyme reactivation by other chaperones such as tubulin (52) and nucleolar protein B23 (53).…”
Section: Discussionsupporting
confidence: 85%
“…However, considering the known three-dimensional structures of spectrins (three-helix bundle and rodlike shape) and that of the chaperones (mostly globular), it is unlikely that spectrin will have structural homology with the chaperones. This has been also observed with the tubulin, which has a tubular structure and is known to have chaperone like activity (17,18).…”
Section: Discussionmentioning
confidence: 57%
“…Among the chaperone proteins not belonging to the Hsp family, ␣-crystallin was first shown to have chaperone-like function in suppressing aggregation of various proteins by heat or by using other agents that induce aggregation (16). Similarly for tubulin, a ubiquitous cytoskeletal protein and the building block unit of the microtubule assembly, it was observed that the protein could also suppress both thermal and nonthermal aggregation of a number of unrelated proteins, and the negatively charged C-terminal tail plays a crucial role for its chaperone like activity (17,18).…”
mentioning
confidence: 99%
“…The N-terminal Region Mediates Substrate Protein Binding-Small molecular chaperones, such as small heat shock proteins, ␣-crystallin, tubulin, and clusterin, prevent protein precipitation by forming soluble HMW complexes (27,(32)(33)(34)(35)(36)(37)(38)(39)(40). We first confirmed that ␣-synuclein also acts in this way to prevent protein precipitation, and then investigated which re- gion of ␣-synuclein was critical for substrate protein binding (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…by forming high molecular weight (HMW) complexes with partially unfolded substrate proteins (27,(32)(33)(34)(35)(36)(37)(38)(39)(40). However, alone sHSPs do not have the ability to protect enzymes from thermal inactivation or to promote their functional refolding after de-naturation (31,39,41,42), although a few exceptional cases with marginal effects have been reported (30,33,(43)(44)(45)(46). sHSPs have, therefore, been classified as "junior chaperones" (47).…”
mentioning
confidence: 99%